Talent is overrated : what really separates world-class performers from everybody else - Colvin, Geoffrey (New York : Portfolio, 2008)
An expansion on the author's popular Fortune article,'What It Takes to Be Great,' builds on his premise about success being linked to the practice and perseverance of specific efforts, in a full-length report that draws on scientific principles and real-world examples to demonstrate his systematic process at work.
The mystery -- Talent is overrated -- How smart do you have to be? -- A better idea -- What deliberate practice is and isn't -- How deliberate practice works -- Applying the principles in our lives -- Applying the principles in our organizations -- Performing great at innovation -- Where does the passion come from? -- Understanding the deepest question about great performance.
Includes bibliographical references (p. 209-219) and index.
Keywords: Work -- Psychological aspects; Performance